Pengaruh Gaya Belajar dan Disiplin Belajar Terhadap Hasil belajar Matematika Siswa - Yasin, Irwan; Sarjana, Ketut; Hikmah, Nurul (FKIP Universitas Mataram, 2025)
This study aims to determine the influence of learning styles and learning discipline on mathematics achievement among Grade XI students at SMAN 1 Kopang in the 2024/2025 academic year. This is a quantitative study using the ex post facto method. The population consists of 98 students, and the sample of 51 students was selected using simple random sampling based on the Taro Yamane formula. Data were collected through questionnaires and tests, and analyzed using linear regression. The relationship between learning styles and mathematics achievement is expressed by the equation Y= 0,501X1 + 27,995, with a correlation coefficient of 0.320, indicating a weak relationship. Meanwhile, the relationship between learning discipline and mathematics achievement is expressed by Y= 0,646X2 + 22,975, with a correlation of 0.435, indicating a moderate relationship. Simultaneously, learning styles and learning discipline together show a relationship with mathematics achievement through Y= 0,459X1 + 0,618X2, with a correlation coefficient of 0.524, categorized as moderate. The coefficient of determination is 24.4%, indicating that both variables simultaneously influence students’ mathematics learning outcomes.